(untitled) (CIPEEX, 2025)
Brazilian agricultural production has developed in such a way that Brazil will be the great supplier of food in the future, but for this development it is necessary to invest in credit lines, loans for the purchase of commodities, acquisition of machinery, preparation of the land. This work aims to study rural credit as an instrument of agricultural policy, its special legislation and its legal nature. The methodology used was deductive, based on the analysis of the doctrines and legislation on the subject. As a result and discussions, it is noted that rural credit is a set of actions and instruments provided for in article 187 of the Federal Constitution of 1988, which the State uses to promote agricultural production. It is the responsibility of the State to promote food supply, and the use of rural credit is fundamental for the social stability of the nation. Second point, such credit is governed by special legislation, mainly by Law No. 4,829 of 1965 and Decree 167 of 1967. These rules created the rural credit cell and establish guidelines for rural financing. Rural credit has its own legal nature, specific sources of funds, beneficiaries and determined investors, in addition to a delegation of competence to the federal administrative authority for its standardization. Its importance is linked to the role of the State in promoting this activity, which results in greater production to feed society. Disregarding this specificity can lead to an inadequate treatment of rural credit. It is concluded that magistrates must consider the aspect of agrarian policy when deciding on issues related to rural credit, and lawyers need to understand this dynamic to establish theses that help in the analysis of the facts. Agricultural policy aims to guarantee the food of society, promoting social peace, because without food there is no dignity or health, and rural production is essential to ensure these benefits.